If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + -4)(4a + -1) = 0 Reorder the terms: (-4 + 4a)(4a + -1) = 0 Reorder the terms: (-4 + 4a)(-1 + 4a) = 0 Multiply (-4 + 4a) * (-1 + 4a) (-4(-1 + 4a) + 4a * (-1 + 4a)) = 0 ((-1 * -4 + 4a * -4) + 4a * (-1 + 4a)) = 0 ((4 + -16a) + 4a * (-1 + 4a)) = 0 (4 + -16a + (-1 * 4a + 4a * 4a)) = 0 (4 + -16a + (-4a + 16a2)) = 0 Combine like terms: -16a + -4a = -20a (4 + -20a + 16a2) = 0 Solving 4 + -20a + 16a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '4'. 4(1 + -5a + 4a2) = 0 Factor a trinomial. 4((1 + -4a)(1 + -1a)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(1 + -4a)' equal to zero and attempt to solve: Simplifying 1 + -4a = 0 Solving 1 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4a = 0 + -1 -4a = 0 + -1 Combine like terms: 0 + -1 = -1 -4a = -1 Divide each side by '-4'. a = 0.25 Simplifying a = 0.25Subproblem 2
Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1Solution
a = {0.25, 1}
| 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 | | 6-0.25f=3 | | 6.4x=0.2816 | | -6t+17=3t-34 | | -23z+234=970 | | 0.4y-8=9-0.6y | | .01x+.10x+.25(31-2x)=3.46 | | 108+4u=2u | | -.8x+2.2=7 | | 5x+21-2x=27 | | -3.7-5x-8.3-2x=-6x+11.4 | | 6.4x=0.2016 | | 4a^2-10=54 | | (72.34)2.1= | | -3(3x+15)-(10-1x)=35 | | 28x-7=26x+7 |